Effectiveness of Civil Servant Retirement Payment Services at PT. Pos Indonesia KCP Perbaungan - Desvira Utami Rahmadini; Muhammad Arif (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Pension is an old age guarantee and is a reward for Civil Servants who have served the State for many years. This study was conducted to determine whether the services provided when paying civil servant pension funds were effective. The research method in this study is a qualitative research method, and the technique of collecting data is observation or direct observation to the research location, conducting interviews, and documentation. The results showed that the service provided by PT. Pos Indonesia Kcp Perbaungan is good but not effective enough. This is because there are several components that are still lacking but are not the most important, such as the absence of queue numbers and office equipment which sometimes experience machine problems. With this research, it is hoped that the company will be able to meet the existing deficiencies in order to achieve effectiveness in service.